ByzRev 02.2020.007: Si Sheppard, Constantinople AD 717–18: The Crucible of History.: Illustrated by Graham Turner. Oxford: Osprey Publishing Ltd 2020. - McMahon, Lucas R. (The Byzantine Review, 2020)
Si Sheppard, Constantinople AD 717–18: The Crucible of History. Illustrated by Graham Turner. Oxford: Osprey Publishing Ltd 2020. 96 pp. -- ISBN: 978-1-4728-3692-2 (paperback: £15.99).